Analisis Keterbatasan Guru Dalam Penggunaan Bahan Ajar Di SD Swasta Cerdas Bangsa Medan - Laurensia M Peranginangin laurensia; Miftahul Jannah Manurung miftahul; Reni Afriani Samosir reni; Wanda Hamidah Harapan wanda; Debora Florentina debora (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
Teachers have an important role in learning in the classroom. Therefore, to carry out meaningful learning for students, one of the teacher’s tasks is to develop teaching materials that are good and attractive to students. Developing teaching materials by teachers serves to make it easier for teachers to implement or process learning in the classroom, so that learning takes place optimally. This study aims to describe the problems of teachers in the use of teaching materials at SD Swasta Cerdas Bangsa Medan. This type of research uses descriptive qualitative research that reveals actual events or facts when the research takes place. Data collection techniques are carried out by interview techniques. The results of the study indicate that, Gura problems in the use of teaching materials include: (1) teachers have difficulty in expressing ideas to develop teaching materials. In this case the teacher has difficulty expressing ideas to develop teaching materials. What is the case, because in developing teaching materials, of course, teachers must pay attention to the potential of students, student development, and relevance to the needs of students (2 teachers rarely make or use learning media. Teachers are rare. Creating learning media, usually teachers only use the media available at school.